Islam Raja Ampat dan Mitos Hantu Cuwig: Benturan Agama, Adat dan Kepercayaan Lokal pada Masyarakat Multikultural di Kampung Lilinta Papua Barat - Nawir, M. Syukri; Yusuf, Muhamad; Kadir, Akhmad (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2020)
The clash of religions, customs, local beliefs gives a distinctive color in the lives of the people of the Raja Ampat Islands. How the myth of Cuwig's mythical influence on religious life in the village of Lilinta in the Raja Ampat-Papua archipelago and in interpreting and reformulate their religious life in response to the myth of Cuwig. Religious knowledge has an important meaning to improve the faith of the community, thus creating religious emotion, encouraging people to do religious actions, although there is still a society believing the mystical, lack of of religious development. The mythical ghost of Cuwig is influenced by the environment. Myths evolved from the simultaneous stories beginning with the emergence of sudden death from the citizens, the problem spread the issue of the science of Cuwig in the intended person.